Investigation of piperazines as human carbonic anhydrase I, II, IV and VII activators. (1st January 2018) - Angeli, Andrea; Chiaramonte, Niccolò; Manetti, Dina; Romanelli, Maria Novella; Supuran, Claudiu T.
Abstract: Four human (h) carbonic anhydrase isoforms (CA, EC 4.2.1.1), hCA I, II, IV, and VII, were investigated for their activation profile with piperazines belonging to various classes, such as N-aryl-, N-alkyl-, N-acyl-piperazines as well as 2, 4-disubstituted derivatives. As the activation mechanism involves participation of the activator in the proton shuttling between the zinc-coordinated water molecule and the external milieu, these derivatives possessing diverse basicity and different scaffolds were appropriate for being investigated as CA activators (CAAs). Most of these derivatives showed CA activating properties against hCA I, II, and VII (cytosolic isoforms) but were devoid of activity against the membrane-associated hCA IV. For hCA I, the K A s were in the range of 32.6–131 µM; for hCA II of 16.2–116 µM, and for hCA VII of 17.1–131 µM. The structure-activity relationship was intricate and not easy to rationalize, but the most effective activators were 1-(2-piperidinyl)-piperazine ( K A of 16.2 µM for hCA II), 2-benzyl-piperazine ( K A of 17.1 µM for hCA VII), and 1-(3-benzylpiperazin-1-yl)propan-1-one ( K A of 32.6 µM for hCA I). As CAAs may have interesting pharmacologic applications in cognition and for artificial tissue engineering, investigation of new classes of activators may be crucial for this relatively new research field.